Escape Room Blueprint: Central Orientation Contagion Crisis. (February 2021) - McLaughlin, Jill L.; Reed, Jessica A.; Shiveley, Jody; Lee, Stephanie
Background: Turnover rate for new graduate nurses at a midwestern community hospital was 30% for the first two years. Centralclinical orientation for new hire registered nurses and care assistants was heavily executed via didactic format. Feedback from instructors suggested boredom and disengagement of learners during these sessions. Post central orientation evaluations resulted in 49% of attendees feeling not "very confident" to apply skills in clinical practice. Methods: Clinical educators created an escape room to improve learner satisfaction, interprofessional communication, and confidence in applying skills in practice. A convenience sample of twenty-three (23)registered nurses and care assistants participated in anescape room, Contagion Crisis, covering basic knowledge of infection control, emergency response, restraints, and drug calculation. Results: Average Likert scores on the post survey forsatisfaction and communication were 4.67 and 4.0 respectively. Confidence in applying skills to practice averaged 4.72. Subjective feedback from participants included enjoyment of a fun, non-pressure environment. Conclusion: Multiple clinical disciplines can use this escape room, as it covers topics fromcentral hospital orientation . Learners preferred the escape room format versus a high-fidelity simulation, due to it being less "high stakes" and not a judgement of individual performance.